2018
DOI: 10.1111/auar.12271
|View full text |Cite
|
Sign up to set email alerts
|

Co‐authorship Network Analysis in the Accounting Discipline

Abstract: The purpose of this study is to explore co‐authorship structures in the accounting discipline through social network analysis. For this purpose, we hand‐collected the authorship data of 10 863 papers published in 22 accounting journals listed on the Web of Science for the period 2000–2016. The findings indicate that the proportion of multi‐author papers has increased over time while the trend away from sole authorship has continued. The network indicators and visualisations reflect that accounting research man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
(285 reference statements)
1
9
0
2
Order By: Relevance
“…between 0 and 1 denotes the proportion of existing links to all possible links in the network (Andrikopoulos & Kostaris, 2017; Gallardo-Gallardo, Arroyo Moliner, & Gallo, 2017; Khan & Wood, 2015; Racherla & Hu, 2010). Third, across the periods, the consistent increase in connectedness and decrease in fragmentation in the network showed that the co-word network became increasingly tight and cohesive(Kılıç et al, 2019;Varga, 2011), because the connectedness index measures the extent to which individual actors are connected in the network, whereas the fragmentation index indicates how the network fragments into clusters(Shimada & Sueur, 2014). The apparently low-density value was not particularly surprising and it was attributable to the large size of the network in our case(Gallardo-Gallardo et al, 2017).…”
mentioning
confidence: 60%
See 4 more Smart Citations
“…between 0 and 1 denotes the proportion of existing links to all possible links in the network (Andrikopoulos & Kostaris, 2017; Gallardo-Gallardo, Arroyo Moliner, & Gallo, 2017; Khan & Wood, 2015; Racherla & Hu, 2010). Third, across the periods, the consistent increase in connectedness and decrease in fragmentation in the network showed that the co-word network became increasingly tight and cohesive(Kılıç et al, 2019;Varga, 2011), because the connectedness index measures the extent to which individual actors are connected in the network, whereas the fragmentation index indicates how the network fragments into clusters(Shimada & Sueur, 2014). The apparently low-density value was not particularly surprising and it was attributable to the large size of the network in our case(Gallardo-Gallardo et al, 2017).…”
mentioning
confidence: 60%
“…The consistent decline in fragmentation and increase in connectedness within the co-word network showed that the auditing discipline is becoming increasingly tight and cohesive (Kılıç et al, 2019;Varga, 2011 Advances in information technology, the rise of the real-time economy, and massive fraud scandals played a major role in the emergence of continuous auditing practices (Eulerich & Kalinichenko, 2018). Researchers have generally tended to study continuous auditing using XML-based accounting systems (Murthy & Groomer, 2004), in an internal auditing context (Gonzalez, Sharma, & Galletta, 2012), to determine whether it enhances financial reporting quality (Lee, Kang, Oh, & Pyo, 2014), to assess how to minimize the cost of continuous audit practices arising from the maintenance of a large dataset (Pathak, Chaouch, & Sriram, 2005;Pathak, Nkurunziza, & Ahmed, 2007), and to evaluate the incremental value of continuous auditing practice (Farkas & Murthy, 2014 ; the drivers of, and obstacles to, big data evolution in audits (Alles, 2015); the consequences of big data in accounting and auditing (Krahel & Titera, 2015); the impact of big data on audit evidence; and audit judgments and financial statement audits (Brown-Liburd, Issa, & Lombardi, 2015;Cao, Chychyla, & Stewart, 2015;Yoon, Hoogduin, & Zhang, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations